Follow the Footsteps of Leonardo Fea: An Example of an Integrative Revision of Freshwater Mussel Taxa Described from the Former British Burma (Myanmar). (27th May 2022) - Bolotov, Ivan N.; Konopleva, Ekaterina S.; Vikhrev, Ilya V.; Win, Than; Lunn, Zau; Chan, Nyein; Gofarov, Mikhail Yu; Kondakov, Alexander V.; Tomilova, Alena A.; Pasupuleti, Rajeev; Subba Rao, Nalluri V.
Abstract : Leonardo Fea, an Italian explorer and traveler, sampled a comprehensive collection of continental Mollusca during his travels throughout the former British Burma (currently Myanmar) in 1885-1887. Cesare Maria Tapparone-Canefri, an Italian malacologist, studied this sample and published a paper with a description of numerous terrestrial and freshwater molluscan taxa new to science. This collection was partly deposited in the Museo Civico di Storia Naturale di Genova (MSNG), Italy and the Indian Museum (ZSI: Zoological Survey of India) in Kolkata. Here, we provide a re-analysis of C.M. Tapparone-Canefri's Burmese Unionidae collection. Our study reveals that the type series of only four nominal taxa described by Tapparone-Canefri as new to science in 1889 are still available in the MSNG, i.e. Unio rectangularis, U. pulcher, U. protensus var. obtusatus, and U. marginalis var. subflabellata . The first taxon is a valid species belonging to the genus Yaukthwa, while U. pulcher and U. protensus var. obtusatus are considered here as junior synonyms of the widespread Lamellidens generosus, and the last nominal taxon corresponds to L. savadiensis . The MSNG collection also contains shell lots of Indochinella pugio pugio, I. pugio paradoxa, Indonaia andersoniana, Radiatula chaudhurii, R. mouhoti haungthayawensis, Lamellidens savadiensis, L. generosus, Yaukthwa nesemanni, and Y. zayleymanensis, most of which were listed in Tapparone-Canefri's work under incorrect names. We revise all the freshwater mussel taxa listed by Tapparone-Canefri based on the original descriptions, available DNA sequences, morphological data, and biogeographic evidence. A freshwater mussel from the Haungthayaw River that was identified by Tapparone-Canefri as Unio exolescens is described here as Trapezoideus mitanensis sp. nov., a fourth species in this small Contradentini genus with a restricted range. Finally, new taxonomic opinions are proposed here for Leoparreysia tavoyensis, Trapezidens dolichorhynchus, Lamellidens generosus, and Lamellidens savadiensis .